PRODUCT, PROCESS, AND SKILL: A COMPREHENSIVE APPROACH TO GRAMMAR TEACHING - Dilrabo Babakulova (Modern American Journals, 2025)
This paper explores a multifaceted approach to grammar teaching based on Batstone’s (1994) classification of grammar instruction into three categories: product, process, and skill. It analyzes and evaluates a series of grammar teaching activities from coursebooks, providing modified versions to better meet learners’ needs across different proficiency levels. Each approach is examined for its pedagogical effectiveness, student engagement, and contextual applicability. The modifications suggested aim to increase interactivity, relevance, and student motivation. The study concludes that a balanced combination of all three approaches—product, process, and skill—enhances both grammatical understanding and practical language use. Emphasis is placed on the role of context, creativity, and learner involvement in grammar instruction.
Keywords: Grammar teaching, product approach, process approach, skill approach, Batstone, language pedagogy, grammar activities, learner engagement, contextual learning, grammar instruction strategies.